A deep dive into the static force transmission of the human masticatory system and its biomechanical effects on the temporomandibular joint. (March 2023) - Sun, Tinghui; Chong, Desmond Y.R.; Shao, Bingmei; Liu, Zhan
Highlights: An advanced finite element model of the human masticatory system was established. Various bite scenarios were simulated. The essential role that TMJs played during the occlusal processes was discussed. Molar occlusal surfaces are the primary force transmission area for clenching. Abstract: Objective: This study aims to investigate the biomechanical behavior and reveal the force transmission patterns of the human masticatory system through advanced three-dimensional finite element (FE) models. Methods: The FE model was constructed according to the medical images of a healthy male adult. It contains full skull structures, detailed temporomandibular joints (TMJs) with discs, complete dentitions, masticatory muscles, and related ligaments. Several static bite scenarios were simulated to demonstrate the effects of bite positions and muscle force recruitments on the force transmission patterns. Results: Molar occlusal surfaces are the primary force transmission region for clenching. Sensitivity analysis demonstrated that the stiffness of the bite substance would not alter the force transmission patterns but could affect the maximum contact stresses on the discs and the occlusal surfaces. During the unilateral clenching tasks, the high-stress region on the discal surfaces shifted ipsilaterally. The presence or absence of the molar cushions would significantly affect the biomechanical response of the masticatory system. Significance: FE analysis is an effective way of investigating biomechanical responses involving complicated interactions. Enriching the static analysis of the masticatory system with a detailed model can help understand better how the forces were transmitted and the significance of TMJs during the clenching process.